PENGARUH ADVERTISING DAN SATISFACTION TERHADAP CUSTOMER LOYALTY (Studi Kasus Pada Pengguna Smartphone Samsung di Fakultas Ekonomi Universitas Dirgantara Marsekal Suryadarma) - Yosepha, Sri Yanthy (JURNAL ILMIAH M-PROGRESS, 2020)
This research aims to determine: a) The effect of advertising on customer loyalty b) The effect of satisfaction on customer loyalty and c) Simultaneously the effect of advertising and satisfaction on customer loyalt for smartphone user (Case study of smartphone user of Samsung at Ekonomi Faculty Dirgantara Marshal This research uses a quantitative approach. The research instrument was in the form of a questionnaire. The sample used amounted to 118 respondents namely students of Economy Faculty, Unsurya, Jakarta., Technique data analysis uses multiple linear regression analysis with using SPSS 22.00 software. The results of this research showed that advertising and satisfaction have a significant effect on the significant which is 40,3 % of customer loyalty while the remainder is explained by other variables not contained in this research.Keywords: advertising, satisfaction, customer loyalty